2009
DOI: 10.1094/cchem-86-1-0100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Presoaking on Textural, Thermal, and Digestive Properties of Cooked Brown Rice

Abstract: Cereal Chem. 86(1):100-105Brown rice kernels (japonica type) were soaked in water at different temperatures (25 or 50°C) before cooking to a moisture content of 20 or 30%. Soaked brown rice was cooked in either the soaking water (SW) or in distilled water (DW) (rice solids to water ratio 1:1.4). Color, texture, and in vitro digestive properties of the cooked rice were examined. When the soaking temperature was higher (50°C vs. 25°C), water absorption and starch leaching were greater. To reach 20% moisture, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The smallest hardness (674 g) of soaked brown rice occurred at 40°C for 5 h. We observed that the soaking temperature played a very important role in the brown rice cooking process. Han and Lim (2009) revealed that the brown rice attained 20 % moisture content during soaking was harder than that of the rice which attained 30 % moisture content when cooked, which is consistent with our results.…”
Section: Hardnesssupporting
confidence: 92%
“…The smallest hardness (674 g) of soaked brown rice occurred at 40°C for 5 h. We observed that the soaking temperature played a very important role in the brown rice cooking process. Han and Lim (2009) revealed that the brown rice attained 20 % moisture content during soaking was harder than that of the rice which attained 30 % moisture content when cooked, which is consistent with our results.…”
Section: Hardnesssupporting
confidence: 92%
“…Nowadays, due to changes in consumer life style and health awareness, brown rice is receiving increased interest as a source of not only energy but also several other healthy attributes (Mir et al 2016). Compared with white rice, brown rice is rich in several health beneficial nutrients such as dietary fiber, gamma-oryzanol (an active component of rice bran), antioxidants, essential amino acids, vitamins and minerals (Cui et al 2010;Han and Lim 2009). Despite its the high nutrient content, brown rice is not well accepted as white rice because of the rough and tough texture making it hard to chew (Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain uniform water absorption and desired texture, it is a common practice to soak the brown rice in water before it is cooked (Han and Lim 2009). However, the simple soaking treatment takes a long time and hinders production efficiency in commercial practice.…”
Section: Introductionmentioning
confidence: 99%
“…The starch molecules in rice are tightly distributed to form fascircular micella, which are unpenetrable to water molecules. During soaking and cooking, the AM and AP located near the surface of the rice could leach out into water at low temperature (Han and Lim, 2009). Along with temperature rise, water permeated into the partially crystallized AM and AP molecules in rice grains, also the starch grains started to absorb water and swell, the starch grains broke down to form unimolecule, and the doublehelix of AM was opened, then AM and AP in starch grains were leached gradually (Janeand Shen,1993).…”
Section: Resultsmentioning
confidence: 99%
“…After filling up the hollows, the appearance of cooked rice displays an uneven structure (Figure 6f). The leached AM in cooking water is relatively smaller and greater mobility than AP, which facilitated themselves entering into the hollows at the surface of the cooked rice (Han and Lim, 2009). When the water was finally boiled off, the leached short-chain AM began to migrate and entered into the hollows at the surface of the cooked rice.…”
Section: Textural Propertiesmentioning
confidence: 99%